GPS-based mobile application for wheelchair patients - Jamuna, Kanaston@P Ganesan (2018)
In this century, the mobile application that created become a part of the application in people life. It helps them make or get things easily without going out of the home. Likewise, the GPS-based Mobile Application for Wheelchair Patients is developed for wheelchair patient to purchase medicine at medicine shop without going the shop. The application also helps to track the arrival of location and it can view by the wheelchair patient after the order placed. The application helps the wheelchair patient who has many problems with going the medicine shop such as sometimes they hard to get transportation and they need depend on other help. Besides that, the wheelchair patient will receive the medicine as a home delivery and seller easy to the save or view the database of sales. So, the objectives of this project are to reduce the problem of wheelchair chair patient faced during purchase medicine at medicine shop and make easy to track the delivery of item by using GPS. In additional, the seller can advertise the medicine details in the user interface will make the user get to know more about various medicine information. It will help the user to purchase good and suitable medicine for them. Moreover, adding delivery service also plays important role in this application for make user easily purchase the medicine.